Efficacy of bioagents on seed germination, vigour, and seedling development in muskmelon (Cucumis melo) hybrid - HIWALE, VISHAL M; MANE, SHRIKANT B; CHAVAN, ASHOK M (The Indian Journal of Agricultural Sciences, 2026)
Improving seed germination and seedling vigour in muskmelon (Cucumis melo L.) remains a significant challenge, especially under variable field conditions that hinder early crop establishment. The use of selected bioagents offers a potential strategy to enhance germination efficiency, seedling growth, and vigour. The experiment was conducted during October 2024 at the Department of Botany, Dr. Babasaheb Ambedkar Marathwada University, Chhatrapati Sambhajinagar, Maharashtra to assess the effects of 36 different individual and combined treatments of bioagents, including Trichoderma spp., Pseudomonas fluorescens, Bacillus spp., and Rhizobium japonicum. The bioagents and their combinations significantly improved seed germination and vigour index, although some treatments showed inhibitory effects. Among the 36 treatments, the combined treatment T1 + T3 (Trichoderma viride and Trichoderma harzianum) recorded the highest seed germination (99.67%), followed by T4 (Trichoderma harzianum, 99%). The combined treatment T4 + T6 (Trichoderma harzianum and Pseudomonas fluorescens) achieved the highest seedling length (20.12 cm) and vigour index (1745.10), closely followed by T4 (17.22 cm; 1705) and T2 + T4 (Trichoderma viride and Trichoderma harzianum, 17.53 cm; 1680.60), indicating a synergistic effect on early seedling growth. The lowest germination was observed in the control (T0), with inhibitory effects noted in T7 + T8 (Pseudomonas fluorescens and Bacillus subtilis), T7 + T11 (Pseudomonas fluorescens + Rhizobium japonicum), T10 (microbial consortium), and T8 (Bacillus subtilis). These findings suggest that specific combinations of compatible bioagents can significantly enhance muskmelon seedling vigour under laboratory conditions.